2015
DOI: 10.1080/15384047.2015.1121348
|View full text |Cite
|
Sign up to set email alerts
|

The role of NANOG transcriptional factor in the development of malignant phenotype of cancer cells

Abstract: NANOG is a transcription factor that is involved in the self-renewal of embryonic stem cells (ES) and is a critical factor for the maintenance of the undifferentiated state of pluripotent cells. Extensive data in the literature show that the NANOG gene is aberrantly expressed during the development of malignancy in cancer cells. ES and cancer stem cells (CSCs), a subpopulation of cancer cells within the tumor, are thought to share common phenotypic properties. This review describes the role of NANOG in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 70 publications
6
73
0
Order By: Relevance
“…Reportedly, Nanog is an example of a gene induced by Tet1 expression. Not only does Nanog have a role in the maintenance of mouse ES cells (20), but also in the maintenance of cancer stem cells, suppression of apoptosis, promotion of cancer progression and metastasis, and angiogenesis (21). These findings suggest that PTEN deficiency drives TET1 and TET1-gene regulation during carcinogenesis; however, the underlying reasons for an increase in the TET1 expression in PTEN deficiency remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, Nanog is an example of a gene induced by Tet1 expression. Not only does Nanog have a role in the maintenance of mouse ES cells (20), but also in the maintenance of cancer stem cells, suppression of apoptosis, promotion of cancer progression and metastasis, and angiogenesis (21). These findings suggest that PTEN deficiency drives TET1 and TET1-gene regulation during carcinogenesis; however, the underlying reasons for an increase in the TET1 expression in PTEN deficiency remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The results of agar colony formation rate assay showed that the supernatants of 1-2F monoclonal cells with different dilution ratios reduced the rate of HUSSLCs agar colony formation in concentration-dependent manner, indicating that 1-2F monoclonal antibodies can inhibit anchorage-independent growth of HUSSLCs and has tumorigenic effect. ABCG2 overexpression contributes to and maintains multidrug resistance of tumor stem cells [35][36][37][38] ; Abnormal expression of Bmi1 contributes to and maintains the self-renewal, unrestricted proliferation and multidrug resistance properties [39][40][41][42] of tumor stem cells; Nanog abnormal expression and functional effect of self-renewal and unrestricted proliferation [43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…Given it is a transcription factor and one that has been shown to be adequate to reprogrammed induced pluripotent cells, it is not surprising that NANOG has a role in tumorigenesis across different cancers [15]. STAT3 seems to be an important downstream effector of NANOG overexpression in cancer cells [12,16].…”
Section: Discussionmentioning
confidence: 99%